2007
DOI: 10.1080/02680930601158901
|View full text |Cite
|
Sign up to set email alerts
|

Discourse structuration in Israel, democratization of education and the impact of the global education network

Abstract: The 1968 structural reform of the education system in Israel was part both of a global process of democratization of education launched after the Second World War and of a larger modernization project in which the social sciences played a crucial role. This dynamic was an expression of a conjunction of interests, in which political forces used research on educational matters in order to advance their socio-political agendas, while researchers used the state's interest in their work and in the 'social problems'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…The neo-Weberian approach includes three key concepts -reformist discourse structuration, knowledge producers as a status group and global education networks. I have analyzed the neo-Weberian approach elsewhere detail (Resnik, 2006(Resnik, , 2007(Resnik, , 2008, therefore I will only outline it here and describe its new dynamics in more detail.…”
Section: Managerial Reforms and The Neo-weberian Theoretical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The neo-Weberian approach includes three key concepts -reformist discourse structuration, knowledge producers as a status group and global education networks. I have analyzed the neo-Weberian approach elsewhere detail (Resnik, 2006(Resnik, , 2007(Resnik, , 2008, therefore I will only outline it here and describe its new dynamics in more detail.…”
Section: Managerial Reforms and The Neo-weberian Theoretical Perspectivementioning
confidence: 99%
“…Discourse structuration and the particular 'social problem' constructed in each country result from the relationship between scholars and political actors that are structured differently in each society (Wittrock, Wagner, & Hollman, 1991). The study of structural reforms after WWII showed that in the case of Israel, the reformist discourse structuration resulted from a strong alliance between knowledge production and central power, namely, between two main actors: Moshe Smilansky, a sociologist of education dedicated to studying inequality of opportunity topics, and Zalman Aranne, the Minister of Education who supported the large scale structural reform and generously funded it (Resnik, 2007). Distinctively, the structuration of the managerial discourse followed a more complex track.…”
Section: Managerial Reforms and The Neo-weberian Theoretical Perspectivementioning
confidence: 99%
“…The framing of the reform as the solution to an impending social problem that threatened the future of Israel-its unity as a nation as well as its economic and scientific developmentpermitted the expansion of the discussion and the incorporation of political actors into the debate. In June 1966, the Knesset appointed a parliamentary committee, the Rimalt Committee, to investigate the structural reform of the elementary and post-elementary education system in Israel (Resnik, 2007). While the Rimalt Committee's recommendations were similar to those of the Prawer Committee before it, the main difference between them lay in the Rimalt Committee's emphasis on social integration (Schmida, 1987, p. 182)-the 'ethnic gap' discourse (Report of the Parliamentary Committee, 1971, pp.…”
Section: Reformist Network In Israel and The Construction Of The 'Ethmentioning
confidence: 99%
“…All these factors appear to be enhanced in classes with a higher level of student composition (e.g., Barr & Dreeben, 1983; Felmlee & Eder, 1983; Oakes, 1985; Gamoran, 1986; Oakes et al ., 1992; Voigt, 1994; Boaler, Dylan, & Brown, 2000; Thrupp et al . 2002; Iturre, 2005; Rumberger & Palardy, 2005; Opdenakker & van Damme, 2007; Harris, 2010; Schofield, 2010). .…”
Section: Conceptualising Compositional Effectsmentioning
confidence: 99%